Pineapple peel bromelain extract improves poultry in vitro protein digestibility - Akit, Henny; Loh, Teck Chwen; Ab Aziz, Muhamad Faris; Foo, Hooi Ling; Zailani, N. S. (Malaysian Society of Animal Production, 2024)
This study aimed to assess the proteolytic activity of pineapple peel crude bromelain extracts using different extractants and its impact on in vitro protein digestibility, simulating poultry digestion. This study compared the proteolytic activity of bromelain extracted using deionized water alone and in combination with 0.02 M dithiothreitol (DTT), 0.02% sodium azide, and 0.02 M ethylenediaminetetraacetic acid (EDTA). Subsequently, the effects of bromelain extracts on protein solubilization and digestibility using a poultry gut simulation model were evaluated. The findings indicated that bromelain extractions using deionized water (82.22 U/mg) and a combination of deionized water + sodium azide + EDTA (87.84 U/mg) exhibited the highest proteolytic activities compared to other extractants (P<0.05). Furthermore, pineapple peel bromelain extracts resulted in up to 24% increase in protein solubility and up to 6% increase in protein digestibility (P<0.05, respectively). Notably, bromelain extracted using deionized water (60.69 U/mg) proved to be the most effective in digesting protein in vitro.